Analyzing the visual characteristics of City and municipal administrative buildings in key cities of Mindanao - Abella, Kristoffer Miguel R. (2019)
The objective of the study is to analyze the visual characteristics of city and municipal halls in key cities of Mindanao, using an architectural character survey method. These city and municipal halls are buildings that serve as the seat of government of the city, and cater to the residents of the area. Twenty-seven city and municipal halls were included in the scope of the study. Through architectural photo documentation and ocular inspection, the exterior and interior of the city and municipal halls were surveyed. The data gathered was then collated and analyzed according to the architectural character guidelines. After analysis, the results show that there is a common architectural character in most of the city and municipal halls included in the study. Many of the buildings studied have similar characteristics. There is a variation in architectural style of the time. These commonalities are due to the building type and the architectural influence from the history and culture of Mindanao. These common characteristics are synthesized into an architectural design, adapted for the selected site. The resulting design translation is made to reflect the architectural character of the city and municipal halls of Mindanao. Further studies are recommended to include more detailed documentation of the various buildings' architectural elements, as well as their history.